Treatment of syncope in tongue cancer with palliative chemotherapy in the intensive care unit: A case report. Issue 35 (August 2019) - Fang, Chongkai; Yang, Liting; Zeng, Guangbi; Huang, Ruilin; Fang, Wei; Chen, Yao; Guan, Jieshan; Li, Peng; Huang, Xuewu; Lin, Lizhu
Abstract: Rationale: Syncope caused by head and neck cancer (HNC) is rare. However, syncope caused by tongue cancer (TC) is even rarer. In TC, syncope is caused by tumor-mediated compression of the carotid sinus and stimulation of the glossopharyngeal nerve. Patient concerns: In this study, we report the case of a 48-year-old male patient who was diagnosed with advanced TC and bilateral cervical lymph node metastasis. On the third day of admission, the patient experienced recurrent syncope with hypotension and bradycardia. Diagnoses: The patient was diagnosed with a well-differentiated squamous cell carcinoma of the tongue along with massive cervical lymph node metastasis and carotid sinus syndrome. Interventions: Initially, symptomatic treatment of syncope boosted the blood pressure and increased the heart rate. Thereafter, a temporary pacemaker was implanted. Finally, chemotherapy was used to control the tumor and relieve syncope. Outcomes: After chemotherapy, the tongue ulcers and cervical lymph node reduced in size; syncope did not recur. Lessons: This case shows that chemotherapy may be a valid treatment option in patients with cancer-related syncope; however, the choice of chemotherapeutic drugs is critical. Intensive care provides life support to patients and creates opportunities for further treatment.